Sclerema Neonatorum Treated Successfully with Parenteral Steroids: An Experience from a Resource Poor Country - Sandeep Shrestha; Nagendra Chaudhary; Sujit Koirala; Ruchi Gupta (Case Reports in Pediatrics)
Sclerema neonatorum is a form of panniculitides characterized by diffuse hardening of subcutaneous tissue with minimal inflammation. It usually affects ill and preterm neonates. Prognosis is usually poor in many cases despite aggressive management. Various treatment modalities (antibiotics, intravenous immunoglobulin, steroids, and exchange transfusion) have been explained in literature. Steroids due to its easy availability and low cost can prove to be lifesaving in such cases, especially in resource poor countries. Here, we report a case of sclerema neonatorum in a one-week preterm baby treated successfully with parenteral steroids and antibiotics.